Multidisciplinary Management of Collegiate Sports-Related Concussions - Knollman-Porter, Kelly; Constantinidou, Fofi; Beardslee, Jennifer; Dailey, Stephen (Seminars in Speech and Language, 2019)
Purpose Collegiate varsity athletes are at risk for sustaining a sports-related concussion, which can negatively impact performance during academic, social, work, and athletic endeavors. Because of the complex nature of concussions and high rates of underreporting by athletes, concussion education, identification, and postinjury care require a collaborative, multidisciplinary approach. Therefore, the purpose of this paper is to describe the specific responsibilities of the team members along with the established pre- and postconcussion procedures of one of the oldest university-based multidisciplinary concussion management programs that is coordinated by speech-language pathology.Method The authors provide a theoretical review of current best practices for the multidisciplinary team along with a discussion of baseline and postconcussion neurocognitive assessment and management procedures directly involving speech-language pathology. Included is a case example illustrating the postinjury procedures utilized by the team.Conclusion Management of the complex sequelae of sports-related concussion for the varsity collegiate athlete necessitates implementation of a multidisciplinary, collaborative approach. Speech-language pathologists' training in the assessment and treatment of brain injury provides the team with an objective perspective in the evaluation and postinjury management of the injured student athlete. While our understanding of concussions has improved greatly over the past two decades, researchers and clinicians on the front lines of care recognize that continued voids exist in our knowledge, with the need to continually explore new methods to identify and manage the complex immediate and potentially long-term ramifications of concussion.
Keywords: concussion; cognition; symptoms; multidisciplinary